The essential vegan air fryer cookbook : 75 whole food recipes to fry, bake, and roast - Challis, Tess (Rockridge Press, 2019)
If you're serious about eating a healthy, plant-based diet but still have cravings for the crispy crunch of fried foods this book has good news for you. The Essential Vegan Air Fryer Cookbook serves up the most comprehensive collection of good-for-you vegan recipes that pack deep-fried taste without all the guilt. From Sweet Miso-Glazed Brussels Sprouts to BBQ Jackfruit Nachos to Cinnamon Crisps, these yummy recipes use the healthiest real food ingredients without ever compromising flavor. But this air fryer cookbook book doesn't just give you healthy recipes--you'll also learn the ins and outs of air frying with expert advice and a handy troubleshooting guide. And yes, you CAN have French fries.